Poverty Dynamics in Benin : a Markovian Process Approach - MEDEDJI, DAMIEN DIEUDONNEE NAPOLEON; HODONOU, Assogba; Gninanfon, Armande; TOTIN, Astherve (My University, 2010)
In this paper the Markov model has been used to analyze poverty dynamics in Benin. Assuming that the observed successive changes in classes of wellbeing at the household level could be considered as a Markov chain, the first-step-analysis method is used to derive several indicators to measure the relevance of poverty reduction policies implemented in Benin. Data used come from a two-year panel of 16,562 households (2006 and 2007). The analysis shows that Benin will attain its objective of 15% extreme poverty, but probably five years later than the target date of 2015. There exists a high level of mobility for wellbeing with a large number of households exiting extreme poverty. The poverty policies implemented between 2006 and 2007 were effective and allowed sustained upward mobility.
Keywords: Markov chain; Poverty dynamics; ordered model; Benin.